Application of Remote Sensing Methods to Monitor Coastal Zones - Luis Pedro Almeida; Rafael Almar (Journal of Marine Science and Engineering, 2020)
In this Special Issue “Application of Remote Sensing Methods to Monitor Coastal Zones” nine original research papers were published, with topics covering a wide range of ranging of remote sensing applications including coastal topography, bathymetry, land cover, and nearshore hydrodynamics [...]